An Evolutionary Dynamic Approach for Designing Wireless Sensor Networks for Real Time Monitoring - Martins, Flávio V C; Carrano, E G; Wanner, E F; Takahashi, R H C; Mateus, G R (2010 IEEE/ACM 14th International Symposium on Distributed Simulation and Real Time Applications, 2010)
The evolution in the microelectronics and embedded systems has expanded the employment of Wireless Sensor Networks (WSNs). The energy limitation of the nodes is a very important restriction of those structures and should be always considered during the network design. The search for energy-efficient WSNs must take into account aspects which are essential for the proper operation of the network, such as area coverage and network connectivity. This paper proposes an evolutionary approach for performing the design of WSNs, considering the dynamic nature of the problem. A genetic algorithm, which aims to maximize the lifetime of the network, is employed for establishing the sequence in which the sensor nodes are activated, ensuring that the minimum coverage (established a priori) and the connectivity constraints are met. Results achieved by the proposed algorithm in a 81-sensor node instance are compared with a former work, in order to validate the approach which is presented here.